Hormone replacement therapy and the prevention of postmenopausal osteoporosis - Gambacciani, Marco; Levancini, Marco (Menopause Review/Przegląd Menopauzalny, 2014)
Fracture prevention is one of the public health priorities worldwide. Estrogen deficiency is the major factor in the pathogenesis of postmenopausal osteoporosis, the most common metabolic bone disease. Different effective treatments for osteoporosis are available. Hormone replacement therapy (HRT) at different doses rapidly normalizes turnover, preserves bone mineral density (BMD) at all skeletal sites, leading to a significant, reduction in vertebral and non-vertebral fractures. Tibolone, a selective tissue estrogenic activity regulator (STEAR), is effective in the treatment of vasomotor symptoms, vaginal atrophy and prevention/treatment of osteoporosis with a clinical efficacy similar to that of conventional HRT. Selective estrogen receptor modulators (SERMs) such as raloxifene and bazedoxifene reduce turnover and maintain or increase vertebral and femoral BMD and reduce the risk of osteoporotic fractures. The combination of bazedoxifene and conjugated estrogens, defined as tissue selective estrogen complex (TSEC), is able to reduce climacteric symptoms, reduce bone turnover and preserve BMD. In conclusion, osteoporosis prevention can actually be considered as a major additional benefit in climacteric women who use HRT for treatment of climacteric symptoms. The use of a standard dose of HRT for osteoporosis prevention is based on biology, epidemiology, animal and preclinical data, observational studies and randomized, clinical trials. The antifracture effect of a lower dose HRT or TSEC is supported by the data on BMD and turnover, with compelling scientific evidence.